2022
DOI: 10.3390/molecules27154704
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicity and Efficacy of Inotodiol as an Anti-Inflammatory Agent Using Animal Model

Abstract: Chaga mushroom (Inonotus obliquus) comprises polyphenolic compounds, triterpenoids, polysaccharides, and sterols. Among the triterpenoid components, inotodiol has been broadly examined because of its various biological activities. The purpose of this study is to examine inotodiol from a safety point of view and to present the potential possibilities of inotodiol for medical usage. From chaga mushroom extract, crude inotodiol (INO20) and pure inotodiol (INO95) were produced. Mice were treated with either INO20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…found that consumption of chaga mushrooms caused oxalate nephropathy, which they determined was due to the high oxalate concentration in the mushrooms. Recently, Nguyen et al 25 . reported that inotodiol does not show any mortality or harm to organs of mice treated with pure inotodiol (95% purity, 20 mg/kg) or crude inotodiol (20% inotodiol, 30 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that consumption of chaga mushrooms caused oxalate nephropathy, which they determined was due to the high oxalate concentration in the mushrooms. Recently, Nguyen et al 25 . reported that inotodiol does not show any mortality or harm to organs of mice treated with pure inotodiol (95% purity, 20 mg/kg) or crude inotodiol (20% inotodiol, 30 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…23 Kikuchi et al 24 found that consumption of chaga mushrooms caused oxalate nephropathy, which they determined was due to the high oxalate concentration in the mushrooms. Recently, Nguyen et al 25 reported that inotodiol does not show any mortality or harm to organs of mice treated with pure inotodiol (95% purity, 20 mg/kg) or crude inotodiol (20% inotodiol, 30 mg/kg). Thus, to the best of our knowledge, there seems to be no definite adverse effect of inotodiol identified, and additional studies are needed to confirm an ideal dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from HaCaT cells using TRIzol (Life Technologies, Carlsbad, CA, USA) according to the manufacturer’s protocol and a previously described method with a slight modification [ 17 ]. cDNA was synthesized from 1 µg RNA by a reverse transcriptional reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there has been a movement to identify novel, safe, and effective molecules that can be used for the treatment of various diseases, including inflammatory diseases. So far, it has been reported that inotodiol exerts anti-inflammatory activity without showing detrimental effects in in vivo and in vitro studies [ 17 ]. Also, inotodiol shows an anti-aging effect under oxidative stress by inhibiting MAPK-NOX5 and NF-κB signaling pathways [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first challenge to overcome is the selection of appropriate animal models to achieve the desired goal. Vertebrate animal models have proven their efficacy in screening inflammatory responses and determining specific molecular therapeutic targets in human medicine ( 23 25 ). In this context, zebrafish (ZF) emerged as an outstanding genetically tractable and practical model for screening the biological process of inflammation in vivo ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%